BRAF Testing in Multifocal Papillary Thyroid Carcinoma. (13th September 2015) - Kimbrell, Hillary Z.; Sholl, Andrew B.; Ratnayaka, Swarnamala; Japa, Shanker; Lacey, Michelle; Carpio, Gandahari; Bhatia, Parisha; Kandil, Emad
Abstract : Background. BRAF V600E mutation is associated with poor prognosis in patients with papillary thyroid carcinoma (PTC). PTC is often multifocal, and there are no guidelines on how many tumors to test for BRAF mutation in multifocal PTC. Methods . Fifty-seven separate formalin-fixed and paraffin-embedded PTCs from twenty-seven patients were manually macrodissected and tested for BRAF mutation using a commercial allele-specific real-time polymerase chain reaction-based assay (Entrogen, Woodland Hills, CA). Data related to histologic characteristics, patient demographics, and clinical outcomes were collected. Results . All mutations detected were BRAF V600E. Seventeen patients (63%) had concordant mutation status in the largest and second-largest tumors (i.e., both were positive or both were negative). The remaining ten patients (37%) had discordant mutation status. Six of the patients with discordant tumors (22% overall) had a BRAF -negative largest tumor and a BRAF -positive second-largest tumor. No histologic feature was found to help predict which cases would be discordant. Conclusions . Patients with multifocal PTC whose largest tumor is BRAF -negative can have smaller tumors that are BRAF -positive. Therefore, molecular testing of more than just the dominant tumor should be considered. Future studies are warranted to establish whether finding a BRAF mutation in a smaller tumor has clinical significance.